Dislocation structure of tungsten irradiated by light ions. (1st February 2023) - Wieluńska-Kuś, B.; Płociński, T.; Schwarz-Selinger, T.; Mayer, M.; Jacob, W.; Ciupiński, L.
Abstract: Single crystalline tungsten samples were irradiated by He, D, and H at room temperature, with a calculated damage level in the peak maximum up to 0.04 dpa and with He up to 0.5 dpa. The dislocation structure of the whole damage zone was investigated perpendicular to the irradiated surface by Transmission Electron Microscopy (TEM) under four different two-beam diffraction conditions g = −200, 020, −110, 110 close to the [100] zone axis, taking bright-field kinematical images. The depth of the damage zone observed by TEM is in good agreement with the damage depth calculated by SRIM. The damage zones of the tungsten samples irradiated by He, D, H up to 0.04 dpa can be subdivided into four subzones. Significant differences in the dislocation structures between the different ion species despite comparable calculated damage levels were found at the depth close to the damage peak maximum. In this depth, the damage zone of tungsten irradiated by He consists of small dense dislocation loops (⩽3 nm) with high strain fields. Irradiation by D creates large dislocation loops with an average diameter of 15–22 nm depending on the set diffraction condition. The damage zone of H-irradiated tungsten is dominated by long dislocation lines at the depth of the damage peak maximum. No transition from dislocation loops to lines was found in the sample irradiated with He up to 0.5 dpa. This is probably due to He bubbles, which hinder the loops to aggregate into lines. This work shows that the displacement damage obtained by the irradiation of tungsten at room temperature with light ions is significantly different to tungsten irradiated to the same calculated damage level by medium to high-mass ions (Wielunska et al 2022 Nucl. Fusion 62 096003 [1]).